Qualidade, intensidade de luz e sistema de ventilação natural no crescimento e análise por headspace – CG/EM na micropropagação de Plectranthus amboinicus - Silva, Sâmia Torres (2016)
The multiplication of medicinal plants by means of micropropagation has many advantages. However, it is necessary to understand how the environmental factors affect growth and the accumulation of in vitro constituents. Plectranthus amboinicus is a medicinal plant, of which essential oil is rich in thymol and carvacrol, antioxidant substances. Thus, the objective was to evaluate the effect of light quality, intensity and the natural ventilation system over the growth and the analysis by headspace-CG-EM of the micropropagated species. Three experiments were conducted. In the experiment for light quality, apical segments where cultivated for 50 days under blue; red; 1 blue:2.5 red; 2.5 blue:1 red; 1 blue:1 red light emitting diodes (LEDs) and cold white fluorescent lamp. In the intensity experiment, nodal segments were cultivated for 83 days under the intensities of 26, 51, 69, 94 and 130 µmol m -2 s -1 , obtained with cold white fluorescent lamps. In the experiment of natural ventilation system (NVS), apical and nodal segments were cultivated for 30 days under conventional system (CS) and natural ventilation system with one (NVS1), two (NVS2) and four (NVS4) porous membranes. In all three experiments, we evaluated the growth and leaf analysis by headspace-CG/EM. The red LED provided greatest length for the shoot and higher total and leaf dry matter for the apical segments. In addition, the red LED resulted in higher accumulation of carvacrol when compared to the fluorescent lamp. The cultivation of nodal segments under the intensity of 69 µmol m -2 s -1 increased the dry matter of leaves, stem and total, as well as the amount of carvacrol. NVS1 provided higher content of leaf, stem, root and total dry matter to apical segments. NVS4 increased the accumulation of carvacrol, but reduced growth. For the nodal segments, NVS2 provided higher content of leaf and total dry matter. In general, the major constituents were α-terpinene, pcimene, γ-terpinene, carvacrol, (E)-caryophyllene and α-trans-bergamotene, with carvacrol present in higher amounts. Thus, this work contributes with relevant information for the in vitro cultivation of the species, and for understanding the changes caused by light quality, intensity and natural ventilation on the volatile chemistry of the leaves analyzed by headspace CG/EM.